Antibacterial metal ion release from diamond-like carbon modified surfaces for novel multifunctional implant materials. Issue 17 (9th August 2016) - Buchegger, Sascha; Vogel, Caroline; Herrmann, Rudolf; Stritzker, Bernd; Wixforth, Achim; Westerhausen, Christoph
Abstract: Abstract : The aim of this study was the synthesis of hard and low-abrasive novel implant materials with built-in time-dependent antibacterial properties, which can be tailored by a well-defined time-dependent and finite release of metal ions. We were able to synthesize such smart implant surfaces employing ECR (electron cyclotron resonance)-plasma on typical titanium implant material by transforming a polymer film into diamond-like carbon (DLC) which contains metal nanoparticles as reservoirs for controlled metal ion release. We found that the amount of released antibacterial metal ions is a biexponential function of time with a high release rate during the first few hours followed by a decreased ion release rate within the following days. To describe our experimental findings, we developed a kinetic model assuming that both nanoparticles near the surface and nanoparticles in the DLC bulk contribute to the total amount of ions released with different time constants.